2014
DOI: 10.15296/ijwhr.2014.20
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Analgesia with Intravenous Paracetamol for Post-cesarean section Pain Control

Abstract: Objectives: Effective pain therapy after cesarean section is essential for parturient comfort and to allow early ambulation to facilitate care of her infant. This study evaluated the analgesic effect of preventive 1gr intravenous paracetamol on postoperative pain and analgesic consumption during the 24 hours after cesarean section. Materials and Methods: One-hundred American Society of Anesthesiologists (ASA) I or II status parturient scheduled for elective cesarean section under spinal anesthesia. Patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
2
8
1
Order By: Relevance
“…The present findings demonstrated that the injection of paracetamol prior to the end of surgery effectively suppressed all possible nociceptor transduction pathways, preventing central sensitization and improving postoperative pain management (5,19,22). In our previous study, we also observed the efficacy of preventive analgesia with paracetamol 1 g in postoperative pain after cesarean section (18).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The present findings demonstrated that the injection of paracetamol prior to the end of surgery effectively suppressed all possible nociceptor transduction pathways, preventing central sensitization and improving postoperative pain management (5,19,22). In our previous study, we also observed the efficacy of preventive analgesia with paracetamol 1 g in postoperative pain after cesarean section (18).…”
Section: Discussionsupporting
confidence: 73%
“…Preventive analgesia was considered to be a suitable definition for both the intraoperative administration of drug and its administration at the end of the surgery for preventing postoperative pain (18). The present findings demonstrated that the injection of paracetamol prior to the end of surgery effectively suppressed all possible nociceptor transduction pathways, preventing central sensitization and improving postoperative pain management (5,19,22).…”
Section: Discussionmentioning
confidence: 51%
“…5 They are secreted into the breast milk which leads to sedation and respiratory depression in newborn infants. 5,6,7 Paracetamol being a non-opioid analgesics is devoid of the potential risks of opioids. 7 It has an established record of safety, efficacy and tolerance in adults.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,7 Paracetamol being a non-opioid analgesics is devoid of the potential risks of opioids. 7 It has an established record of safety, efficacy and tolerance in adults. 8 It is the first line drug recommended by the World Health Organization (WHO) in analgesic ladder approach for pain management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation